Airway Closure and Expiratory Flow Limitation in Acute Respiratory Distress Syndrome - Guérin, Claude; Cour, Martin; Argaud, Laurent (Frontiers in Physiology, 2022)
Acute respiratory distress syndrome (ARDS) is mostly characterized by the loss of aerated lung volume associated with an increase in lung tissue and an intense and complex lung inflammation. ARDS has long been associated with the histological pattern of diffuse alveolar damage. However, diffuse alveolar damage is not the unique pathological figure in ARDS and it can also be observed in settings other than ARDS. In COVID-19 related ARDS the impairment of lung microvasculature has been pointed out. The airways, and of notice the small peripheral airways, may contribute to the loss of aeration observed in ARDS. High resolution lung imaging techniques found that in specific experimental conditions small airway closure was a reality. Furthermore, low-volume ventilator-induced lung injury, also called atelectrauma, should involve the airways. Atelectrauma is one of the basic tenet subtending the use of positive end-expiratory pressure (PEEP) set at the ventilator in ARDS. Recent data revisited the role of airways in humans with ARDS and provided findings consistent with expiratory flow limitation and airway closure in a substantial number of ARDS patients. We discussed the pattern of airway opening pressure disclosed in the inspiratory volume-pressure curves in COVID-19 and in non-COVID-19 related ARDS. We also discused the functional interplay between airway opening pressure and expiratory flow limitation displayed in the flow-volume curves. We discussed the individualization of PEEP setting based on these findings.